Analisis Faktor-Faktor Penerimaan E-Museum Menggunakan Technology Acceptance Model (TAM) : Studi Kasus: www.museumindonesia.org - Saktian Purborini; Tri Lathif Mardi Suryanto; Anita Wulansari (Lembaga Pengembangan Kinerja Dosen, 2025)
The low level of visits to museums compared to other tourist destinations is largely due to the lack of interactive activities and the need for direct guidance in accessing collection information. Although an e-museum platform based on virtual reality technology has been available through museumindonesia.org as a solution to physical limitations and an effort to attract the interest of the younger generation, the extent to which the public accepts this innovation is still unknown. The lack of understanding of the perception of ease and usefulness in using services is an important reason to conduct an evaluation using the TAM approach. This study aims to identify and analyze factors that influence the intention and behavior of using e-museum services, in order to provide a strategic foundation for the development of web-based museum service management. The total respondents used in this study were 120 people. The analysis method used was the Path Analysis method. The results showed that most of the constructs in the model had a significant relationship. Facilitating Conditions were proven to have an influence on Perceived Ease of Use and Perceived Usefulness. Furthermore, Perceived Ease of Use contributes to forming Perceived Usefulness and attitudes towards use (Attitude Toward Using). Among all variables, Perceived Usefulness has the strongest influence on Behavioral Intention, with the highest coefficient value of 0.72. In addition, attitudes toward use also play a role in forming behavioral intentions, which in turn affect actual usage behavior. The results of the analysis show that perceptions of ease of use are a key element in forming perceptions of system usefulness. Overall, the five main variables of Facilitating Condition, Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, and Behavioral Intention have a significant contribution to the acceptance of e-Museum technology.